Implementasi Strategi Peer Lessons pada Mata Pelajaran IPA dalam Meningkatkan Motivasi Belajar Peserta Didik Kelas IV di MI Masyariqul Anwar 4 Bandar Lampung - Juwantara, Ridho Agung; Yulita, Yulita Dwi Lestari (STKIP PGRI Bandar Lampung, 2022)
The purpose of this study was to determine the application of peer lessons strategy in increasing students' motivation to learn in the science lesson of Gaya material in class IV MI Masyariqul Anwar 4 Bandar Lampung. This research uses a qualitative approach with the type of classroom action research. The sequence of research activities includes planning, implementation, observation, and reflection. In collecting data, the author uses observation strategies, measurement of learning outcomes tests, interviews and documentation. As for the analysis used descriptive qualitative analysis techniques. The conclusion of the study shows that the application of the peer lessons strategy can increase the learning motivation of fourth grade students at MI Masyariqul Anwar 4 Bandar Lampung. This can be seen by the significant increase in students' learning motivation. Prior to the implementation of the peer lessons strategy, students' learning motivation was very low for science lessons. After applying the peer lessons learning strategy, the learning motivation of students from cycle 1 to cycle II continued to increase so that it reached a total of 88.2%.